Exploring Talent Management Processes and their Effect on Talent Retention within the Western Cape Department of the Premier (DotP) - Barties, Biondi Neil (Stellenbosch : Stellenbosch University, 2020)
Thesis (MPA)--Stellenbosch University, 2020.